The changing British party system, 1945-1979 - Finer, S. E. (Washington : American Enterprise Institute for Public Policy Research, 1980)
In this study, the author first, justified the subject, the year 1945 as his starting point, and his treatment during the aforementioned year of the British party system.
Includes bibliographical references: p. 233-237.
ne 22/01/2019
Loans
Keywords: Political parties